2016
DOI: 10.22364/bjmc.2016.4.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Technological Aspects of the Gamification Model for e-Learning Participant's Engagement

Abstract: Abstract. Gamification has been a popular object of researches in various fields. Many researches were made on various aspects of gamification and just very few were oriented to the influence of technological aspects for e-learning participant's engagement. The challenge for our designed model was to find out the new effective ways for the engagement of the students. This paper analysis the prevailing technological aspects and technologies used in e-learning process as well as implementation of various technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Studies on gamified e-learning revealed that gamification had a positive impact, increasing students' levels of motivation (e.g., Aleksic ́-Maslac ́et al, 2018; Hamzah et al, 2015;Hassan et al, 2021;Kaufmann, 2018;Monterrat et al, 2014;Shi et al, 2013). The findings also showed an increase in students' levels of engagement with the lessons (e.g., Bouchrika et al, 2021;Gudoniene et al, 2016;Katsigiannakis & Karagiannidis, 2017;Mohamad et al, 2017;Muntean, 2011;Poondej & Lerdpornkulrat, 2019;Rutkauskiene et al, 2016;Wongso et al, 2014).…”
Section: How?mentioning
confidence: 83%
See 1 more Smart Citation
“…Studies on gamified e-learning revealed that gamification had a positive impact, increasing students' levels of motivation (e.g., Aleksic ́-Maslac ́et al, 2018; Hamzah et al, 2015;Hassan et al, 2021;Kaufmann, 2018;Monterrat et al, 2014;Shi et al, 2013). The findings also showed an increase in students' levels of engagement with the lessons (e.g., Bouchrika et al, 2021;Gudoniene et al, 2016;Katsigiannakis & Karagiannidis, 2017;Mohamad et al, 2017;Muntean, 2011;Poondej & Lerdpornkulrat, 2019;Rutkauskiene et al, 2016;Wongso et al, 2014).…”
Section: How?mentioning
confidence: 83%
“…In addition, some researchers studying teaching programming in e-learning environments presented theoretical frameworks for the inclusion of gamification in teaching, while others conducted studies to demonstrate how gamification can be used to overcome problems related to low levels of engagement, which is one of the main problems associated with e-learning. (e.g., Bernik et al, 2017;Gafni et al, 2018;Gudoniene et al, 2016;Piteira & Costa, 2017;Schatten & Schatten, 2019;Swacha & Baszuro, 2013).…”
Section: Where?mentioning
confidence: 99%
“…For example, the ability to catch a Pokémon in a game is an abstraction of a larger probability equation. Therefore, games have often been leveraged for learning [40]. There is an abundance of support for educational games, serious games, and gamification [36,41,42]; these games and apps aim to computerize aspects of existing evidence-based therapies.…”
Section: The Use Of Games Related To Mhmentioning
confidence: 99%
“…For example, the ability to catch a Pokémon in a game is an abstraction of a larger probability equation. Therefore, games have often been leveraged for learning [ 40 ]. There is an abundance of support for educational games, serious games, and gamification [ 36 , 41 , 42 ]; these games and apps aim to computerize aspects of existing evidence-based therapies.…”
Section: Introductionmentioning
confidence: 99%